PENGARUH PELATIHAN TERHADAP KINERJA PEGAWAI PADA PERUM BULOG UNIT KECAMATAN MUARA TELANG KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN - Ikhwan Iswahyudar; Hamid Halin; Roswaty Roswaty (Jurnal Ilmiah Ekonomi Global Masa Kini)
Training is carried out in order to develop human resources and is able to add knowledge and skills that will ultimately affect employee performance. The aim of the study was to find out the effect of Training on Performance Employees at Perum BULOG in unit of Muara Telang sub-District of Banyuasin Regency of South Sumatra Province. In this study, quantitative descriptive method  was used. The technique for analyzing the data was simple linear regression analysis. The sample was all employees who worked at Perum BULOG Muara Telang sub-District unit of Banyuasin Regency, South Sumatera Province with a total number of 54 respondents. From the result of SPSS program, it showed that t-obtained was 7,547 and t-table was 1,674, and the significant level was 0.000 which was less than 0,05 so t-obtained> - table, it means that Ho was rejected, which can be stated that training partially had a significant effect on employee performance. From the result of correlation, it indicated that there was a strong correlation between training variable and employee performance variable, it could be seen from the correlation coefficient which was 0,723 or 72,3%, Then the result of coefficient of determination (R2) was 0,523 or 52,3% from the effect of training variable on employee performance variable at Perum BULOG in Muara Telang sub-District unit of Banyuasin regency of South Sumatera Province, while the rest was 47,7% affected by other factors which was not explained in this study.Keywords : Training, Employee Performance, Human Resource Management